Economics of Business Research on Customers’ Retention and Sales Improvement in Supermarkets - Adebayo, OLOIDI Gabriel; Oladimeji, OLUWALANA Lucas (IJRDO - Journal of Business Management, 2015)
In recent times, the supermarkets around the globe have been so supper among markets that their activities have caught the mercy of various professionals and have attracted much attention. The competitive eloquence is an embellishment of the mystery surrounding their survival. This study has aimed at succinctly contributing to successful operation of these supermarkets through business research. A particular supermarket was taking as a case study, which can be adjustably applied to any other supermarket. A business research was initiated, collecting data on various business activities, customers and competitors. The recency, frequency and monetary (RFM) model was used to sieve various customers who can score RFM of about 280 out of a total of 555 thereby inferring customers with loyalty and hence are those that matter. The regression model was used to initiate a sales forecast from the research data and subsequently where the sales target is derived. Other various aspect of the philosophy of retaining, and winning more customers, dovetailing to improving sales, from experts and professional, formed the dynamic force behind the achievement of the business research outcome. It is recommended that supermarket managers should study the findings in the paper and apply to their situation giving the latitude for necessary adjustments.